Customer Relationship Management System Integration Boosts Customer Satisfaction and Loyalty in Banking - Fadilah Zalzabilah; Nurhadi Nurhadi (Academia Open, 2025)
General Background: The rapid advancement of digital technology has transformed business operations, particularly in the banking sector, where customer relationships are a key determinant of competitive advantage. Specific Background: In the context of Indonesian banking, institutions such as Bank BRI face increasing competition and must therefore adopt innovative systems to enhance service quality and customer experience. Knowledge Gap: Despite the acknowledged importance of Customer Relationship Management (CRM), limited empirical evidence exists regarding the extent to which CRM system integration directly and indirectly affects customer satisfaction and loyalty in local banking units. Aims: This study aims to examine the impact of CRM system integration on customer satisfaction and loyalty at Bank BRI KCP Unit Sorowako, with customer satisfaction as a mediating variable. Results: Using quantitative analysis involving 100 respondents and statistical tests such as the t-test and path analysis, results indicate that CRM integration significantly enhances satisfaction and loyalty, both directly and through mediation. Novelty: The study provides empirical proof that satisfaction serves as a strong mediator, emphasizing the indirect pathway as more influential than the direct effect. Implications: These findings underscore the strategic importance of optimizing CRM systems to deliver faster, more personalized services that drive sustained customer loyalty and organizational growth. Highlights: CRM integration enhances both direct and indirect effects on satisfaction and loyalty. Customer satisfaction acts as a key mediator between CRM and loyalty. Optimizing CRM systems supports personalized service and long-term customer retention. Keywords: Customer Relationship Management, Customer Satisfaction, Customer Loyalty, Digital Banking, System Integration